Single cell sequencing reveals endothelial plasticity with transient mesenchymal activation after myocardial infarction. (25th November 2020) - Tombor, L; John, D; Glaser, S.F; Luxan, G; Forte, E; Furtado, M; Rosenthal, N; Manavski, Y; Fischer, A; Muhly-Reinholz, M; Looso, M; Acker, T; et al.
Abstract:  : After myocardial infarct (MI), followed by ischemia and scar formation, interstitial cells play key roles in the adaptation to injury. Endothelial cells (ECs), for instance, can clonally expand, migrate into the infarct area and facilitate crucial functions promoting revascularization, reestablishment of oxygen supply and secretion of paracrine factors. Moreover, ECs can transiently undergo changes towards a mesenchymal phenotype (Endothelial-to-mesenchymal transition; EndMT). Whether this process contributes to long-term cardiac fibrosis or helps to facilitate post-ischemic vessel growth remains controversial. Here, we aim to delineate kinetics and characteristics of phenotypic changes in ECs with single cell RNA-sequencing (scRNA-seq). We performed a time course (homeostasis or 0 day (d), 1d, 3d, 5d, 7d, 14d, 28d post-MI) in mice and isolated the non-cardiomyocyte fraction for scRNA-seq (n=35, 312 cells). Pecam1/Cdh5 double positive ECs showed expression of apoptosis, hypoxia and inflammation markers at 3d. Bioinformatic cell cycle analysis predicted high association with proliferative capacities at 3d, indicative of EC turnover post-MI. Metabolism, recently linked to regulate EndMT, was altered. We found genes of the glycolysis and the TCA-cycle pathway upregulated at 1d to 3d, and a decrease of fatty acid signaling genes. At 3d, mesenchymal markers Fn1, Vim, S100a4, Serpine1 transiently increased compared to homeostasis (>1.6-fold, p<0.05) together with a reduction of EC genes such as Pecam1. Interestingly, mesenchymal transition was transient and returned to baseline levels at 28d after MI. Cell fate trajectory analysis confirmed these findings by identifying an EC state characterized by high proliferation and mesenchymal but low EC properties. At 3d to 7d the majority of the ECs were assigned to this state, based on their transcriptomic profile. We additionally used Cdh5-CreERT2; R26-mT/mG mice followed by scRNA-seq to trace the fate of ECs. Bioinformatic analysis of GFP-positive ECs confirmed the gain in mesenchymal marker but revealed no full transition to the mesenchymal state at later timepoints. This suggests a transient mesenchymal activation of ECs rather than a complete lineage transition. We further induced EndMT with TGF-β2 in ECs in vitro and observed reversibility of the phenotype after withdrawal of the stimulus. After treatment, ECs upregulated various mesenchymal marker genes. Withdrawal of TGF-β2 at 3d or 7d, reverted expression to baseline levels. We further determined DNA methylation of EndMT gene loci to assess if TGF-β2 leads to a true fate change but did not observe changes after TGF-β2 stimulation and withdrawal. Taken together, our data suggests that ECs undergo a transient mesenchymal activation concomitant with a metabolic adaptation early after MI but do not acquire a long-term mesenchymal fate. This activation may facilitate EC migration and clonal expansion to regenerate the vascular network. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Center of Cardiovascular Research (DZHK), Deutsche Forschungsgemeinschaft (DFG) CRC1366 Project B4